Common Domains of Core Competencies for Hospital Health Care Providers in Armed Conflict Zones: A Systematic Scoping Review. Issue 4 (27th August 2020) - Mani, Zakaria A.; Kuhn, Lisa; Plummer, Virginia
Abstract: Introduction: High rates of mortality and morbidity result from disasters of all types, including armed conflicts. Overwhelming numbers of casualties with a myriad of illnesses and patterns of injuries are common in armed conflicts, leading to unpredictable workloads for hospital health care providers (HCPs). Identifying domains of hospital HCPs' core competency for armed conflicts is essential to inform standards of care, educational requirements, and to facilitate the translation of knowledge into safe and quality care. Objective: The objective of this study is to identify the common domains of core competencies among HCPs working in hospitals in armed conflict areas. Methods: A scoping review was conducted using the Joanna Briggs Institute framework. The review considered primary research and peer-reviewed literature from the following databases: Ovid Medline, Ovid EmCare, Embase, and CINAHL, as well as the reference lists of articles identified for full-text review. Eligibility criteria were outlined a priori to guide the literature selection. Results: Four articles met the inclusion criteria. The studies were conducted in different countries and were published from 2011 through 2017. The methods included three surveys and one Delphi study. Conclusion: This review maps the scope of knowledge, skills, and attitudes required by HCPs who are practicing in hospitals in areas of major armed conflict. Incorporation of identified core competency domains can improve the future planning, education, and training, and may enhance the HCPs' response in armed conflicts.